Gout and amyloidosis. Issue 6 (December 1980) - Levo, Y; Shalev, O; Rosenmann, E; Eliakim, M
Abstract : Two patients with gout and amyloidosis are reported. In contrast with other forms of chronic arthritis gout is apparently not associated with an increased incidence of amyloidosis. The possible reasons for this exception are discussed.